Optimizing Human Development: The Relevance of Hasan Langgulung's Concept of Islamic Education in the 21st Century - Fadlillah, Nilna; Bakar, M. Yunus Abu; Assegaf, Abd. Rachman (Jurnal Penelitian Pendidikan Islam, 2023)
This article is written to explain i) the concept of fitrah and khalifah from Hasan Langgulung's perspective, ii) Hasan Langgulung's Islamic education thought, and iii) the relevance of Hasan Langgulung's Islamic education concept to the development of human potential in the 21st century. The research method used in this research is qualitative-descriptive with the type of library research, with content analysis and interpretative methods. This research is expected to be the basis for designing progressive educational policies and forming individuals who can face the dynamics of change and challenges of the 21st century. According to Hasan Langgulung, in carrying out his responsibility as caliph, humans are equipped with various potentials (fitrah, human intellect, freedom of will, spirit, qalb, nafs) that need to be developed through education. Langgulung's concept of Islamic education emphasizes the development of human potential through the optimization of human intellect, creativity, the ability to work together, continuous education, and technology in education. In the 21st century, Hasan Langgulung's Islamic concept can be applied in forming "pious human beings" who are productive innovative, and contribute positively to building a "pious society". Keywords: Hasan Langgulung, 21st-century education, human potential, fitrah, khalifah